The Mental Image of France in the Jordanian Public Opinion after the Insulting Drawings of the Messenger (Peace and Prayers be Upon Him): : A Field Study (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aims to identify the image of France in the Jordanian public opinion, especially after the publication of the insulting cartoons of the messenger (peace and prayers be upon Him). This study is considered a descriptive study. Within its framework, the survey method was relied upon, and the electronic questionnaire tool was used to collect information from the study sample of (370) individuals from Jordanian public opinion. The study reached the following results:- The image of France is negative, especially after the publication of the offensive cartoons of the messenger (peace and prayers be upon Him), and that the positive mental image of France in Jordanian public opinion diminished after the incident of publishing the offensive cartoons.- It turned out that the cartoons insulting the Prophet (peace and prayers be upon Him) had a negative impact on Jordanian-French relations in various fields, especially economic ones.- It appears that there is a very strong impact of campaigns rejecting cartoons insulting to the Messenger (peace and prayers be upon Him) from the point of view of Jordanian public opinion.- It is evident that the best way to defend the Messenger (peace and prayers be upon Him) is to boycott the products and goods of countries that allow the publication of cartoons insulting to the Messenger (peace and prayers be upon Him).- It is shown that the Arab media are the ones that follow the issue of cartoons insulting to the Messenger (peace and prayers be upon Him) the most.- It has turned out that social media platforms are the most reliable media and communication means in identifying the issue of publishing cartoons insulting to the Messenger (peace and prayers be upon Him).
Keywords: Mental Image; France; Public Opinion; Offensive Cartoons of Prophet Mohammad (peace and prayers be upon Him).